Retourner en forêt quinze ans après sa thèse : quelle place nouvelle pour le paysage dans la gestion forestière depuis le début des années 2000 ? - Véronique Fourault-Cauët (Projets de Paysage)
Following up on a thesis, this article re-examines the role of the landscape in two bodies of forestry documents dating from 2006 to 2018. Based on recent publications of the review Revue forestière française and forestry charters signed in the Provence-Alpes-Côte d’Azur (PACA) region, the definition and implementation of the notion of the landscape by forestry stakeholders is examined. This notion of the landscape is increasingly employed as a theoretical tool for analysing a territory and its evolution, however it does not seem to have acquired an operational dimension. References to landscape management, which were prevalent in the 1980s and 1990s, are becoming rarer, whereas landscape ecology, which is used in scientific research on forests, is hardly ever referred to in the more operational documents. In this sense, the documents studied appear to be consistent with the broader changes in the way the landscape is considered in scientific research and land use planning. The literature bears witness to gradual change over a long period of time which, from a methodological point of view, justifies going back into the “field" or more precisely re-examining the research "object" at regular intervals.